Between the metropole and the postcolony: on the dynamics of rights’ machinery from the northwestern tribal belt to the “mainland” Pakistan: - Nasir, Muhammad Ali (Environment and planning. D, Society and space, 2015)
Recent analyses have critically evaluated the connection of abstract rights with territorial nation-states. This article extends those findings by analyzing the...
Gesehen am 10.08.2020